Software and Hardware Control System for Implementing the Balance Error Scoring System - Oksana Blavt; Gennadii Iedynak; Lesia Galamanzhuk; Tetyana Helzhynska; Yurii Kachurak; Yulia Mykhalskа; Liubov Levandovska; Rostyslav Tymkovych (Physical Education Theory and Methodology)
Objectives. The study aimed to determine the degree of reliability and validity of the “Balance Error Scoring System” (BESS) for students after blast TBI implemented by the developed software and hardware control system.